Racial Disparities in Occult Hypoxemia and Clinically Based Mitigation Strategies to Apply in Advance of Technological Advancements. - Chesley, Christopher F.; Lane-Fall, Meghan B.; Panchanadam, Venkat; Harhay, Michael O.; Wani, Arshad A.; Mikkelsen, Mark E.; Fuchs, Barry D. (Respiratory Care, 2022)
BACKGROUND: Pulse oximetry is the mainstay of patient oxygen monitoring. Measurement error from pulse oximetry is more common for those with darker skin pigmentation, yet this topic remains understudied, and evidence-based clinical mitigation strategies do not currently exist. Our objectives were to measure the rate of occult hypoxemia, defined as arterial oxygen saturation (SaO2) < 88% when pulse oximeter oxygen saturation was between 92-96%, in a racially diverse critically ill population; to analyze degree, direction, and consistency of measurement error; and to develop a mitigation strategy that minimizes occult hypoxemia in advance of technological advancements. METHODS: We performed a multi-center retrospective cohort study of critically ill subjects. RESULTS: Among 105,467 paired observations from 7,693 subjects, we found occult hypoxemia was more common among minority subjects. The frequency of occult hypoxemia was 7.9% versus 2.9% between Black and white subjects, respectively, (P < .001). Pulse oximeter measurement errors were inconsistent throughout a patient encounter, with 67% of encounters having a range of intra-subject measurement errors > 4 percentage points. In 75% of encounters, the intra-subject errors were bidirectional. SaO2 < 88% was less common at higher pulse oximeter oxygenation ranges (4.1% and 1.8% of observations among Black and white subjects at a pulse oximeter threshold of 94-98%). Although occult hypoxemia was further reduced at oxygenation saturation range 95-100%, the frequency of hyperoxemia (partial pressure of arterial oxygen > 110 mm Hg) became more common, occurring in 42.3% of Black and 46.0% of white observations. CONCLUSIONS: Measurement error in pulse oximetry is common for all racial groups, but occult hypoxemia occurred most commonly in Black subjects. The highly variable magnitude and direction of measurement error preclude an individualized mitigation approach. In advance of technological advancements, we recommend targeting a pulse oximetry saturation goal of 94-98% for all patients.